Identifying a Milk-Replacer and Weaning Strategy for Holstein Calves Using Automated Behavioral Measures of Lying and Environmental Enrichment Device Use - E. M. Bortoluzzi; T. M. Hill; L. L. Deikun; L. A. Ruiz; M. J. Goering; T. S. Dennis; F. X. Suarez-Mena; J. D. Quigley; R. L. Schlotterbeck; M. V. Alonso; R. Mazloom; M. Jaberi-Douraki; et al. (Kansas Agricultural Experiment Station Research Reports, 2019)
In dairy production, “weaning readiness” is often based on solid feed intake. The goal of this study was to determine weaning readiness using feed-intake, lying-behaviors, and the use of an environmental enrichment device (EED) in calves that underwent 1 of 4 milk-replacer and weaning protocols. Twenty-eight male Holstein calves (95 ± 2.6 lb BW at 1 d of age) were housed in individual pens and initially fed one type of milk replacer (25% crude protein (CP), 17% fat, 1.45 lb of dry matter (DM)) via nipplebuckets twice a day (AM and PM), and one type of textured calf starter (ad libitum; 20% CP and 37% starch). At age 3 days, calves were randomly assigned to one of the four nutrition-weaning strategies: 1. MOD-STEP - 1.46 lb per day of milk replacer; 2-step weaned, initiated at age 6 weeks, completed 3 days later; 2. HI-STEP - 2.4 lb per day of milk replacer; 2-step weaned, initiated at age 5 weeks and completed 1 week later; 3. HI-LATE - 2.4 lb per day of milk replacer; 2-step weaned, initiated at age 7 weeks and completed 1 week later; and 4. HI-GRAD - 2.4 lb per day of milk replacer; 5-step weaned, initiated at age 6 week and completed 2 weeks later. Each calf’s pen had an EED, which included a dummy-nipple attached to a bottle and holder. A sensor and automated logger tracked each event (1 Hz) that the calf manipulated the EED (25 Hz sensitivity). Each calf was fitted with an accelerometer on the back leg to automatically measure lying behaviors. The device collected the y-axis (lie vs. stand) and z-axis (right or left percent during lying) of the calf every minute. For this experiment, 3-day sample periods were analyzed before and after weaning was initiated. In addition, the 3 days following weaning-completion were sampled. Feed intake among MOD-STEP calves increased by 1.0 ± 0.19 lb after the first bottle was removed (P≤ 0.05), and then by 1.5 ± 0.19 SE lb after completion of weaning (P≤ 0.05). The use of EED did not change among MOD-STEP calves (P>0.05), but after weaning, they increased their lying time, especially on their left side (P≤ 0.05). These changes in lying-behaviors may indicate increased comfort and maturity of the rumen. On the contrary, calves in the HI-STEP treatment ate the least amount of feed overall (P<0.05), and they used the EED the most (P>0.05). Calves in the HI-STEP treatment showed reduced lying bouts after weaning (P≤ 0.05), but no other lying-measures changed (P>0.05). The HI-LATE calves had similar feed intake and EED use compared to MOD-STEP calves. These findings suggest that weaning age needs to be more than 8 weeks for calves fed 2.4 lb of milk replacer per day. Gradual weaning may also improve feed intake and reduce EED use. When calves were gradually weaned starting at age 6 weeks and completed at age 8 weeks, they had the same amount of solid feed intake as HI-LATE calves. More research is needed to determine if increased feed intake and reduced EED use are also indicators that cross-sucking is less likely to occur when calves are grouped after weaning.
Keywords: weaning; sucking behaviors; lie behavior; high plane nutrition; milk replacer